Mohawk - Lajiness, Katie (2019)
introduces readers to the Mohawk people. Text covers traditional ways of life, including social structure, homes, food, art, clothing, and more. Also discussed is contact with Europeans and American settlers, as well as how the people keep their culture alive today. Table of contents, map, fun facts, timeline, glossary, and index are included.
Includes index.
Ages 7-10
Keywords: Mohawk Indians -- History -- Juvenile literature; Mohawk Indians -- Social life and customs -- Juvenile literature